Buddhist stories - Dahlke, Paul. (India : Winsome books, 2011)
The book is a collection of popular Buddhist stories. Thestories include "Death and Life"; "Architectof his Fate"; "The Love of Humanity"; "Nala theSilent", and "Renunciation". The stories highlights differentaspects of Buddhism.
Keywords: Buddhism -- Fiction; Buddhism